2017
DOI: 10.1159/000455333
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Adiposity Predictors of Metabolic Syndrome in the Elderly

Abstract: Background: Adiposity indicators can be used as predictors of cardiovascular risk in the elderly. However, there are only a very few studies that deal with the accuracy of adiposity indicators as predictors of metabolic syndrome (MS) in the elderly. We evaluated the performance of adiposity indicators of MS prediction in the elderly. Methods: A cross-sectional study with 203 elderly people of both genders. Variables: MS defined by harmonized criteria, waist circumference (WC), waist-to-height ratio (WHtR), con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 22 publications
7
40
1
Order By: Relevance
“…Another study on Iranian elderly men identified a higher cutoff point than the one found in the present study, 0.58 (AUC=0.68; 95% CI:0.60 -0.75) [4]. A study conducted in Salvador, Brazil, with 203 elderly individuals residing in a long-term institution in Salvador, identified a cut-off point for the MetS predictor WHeR equal to that of the present study for males, 0.55 (AUC=0.89, 95% CI:0.71-0.98), with sensitivity and specificity values of 0.92 and 0.90, respectively [11].…”
Section: Discussionsupporting
confidence: 38%
See 2 more Smart Citations
“…Another study on Iranian elderly men identified a higher cutoff point than the one found in the present study, 0.58 (AUC=0.68; 95% CI:0.60 -0.75) [4]. A study conducted in Salvador, Brazil, with 203 elderly individuals residing in a long-term institution in Salvador, identified a cut-off point for the MetS predictor WHeR equal to that of the present study for males, 0.55 (AUC=0.89, 95% CI:0.71-0.98), with sensitivity and specificity values of 0.92 and 0.90, respectively [11].…”
Section: Discussionsupporting
confidence: 38%
“…This study, conducted on 113 elderly women from Viçosa (MG), found a WHR cutoff point of 0.6 (AUC=0.67; 95.0% CI:0.58 -0.76) in MetS, with a sensitivity of 73.3% [22], a similar result to the one found in the present study (0.59). In another Brazilian study with institutionalized elderly in Salvador, the sample consisted of 77.8% women, showing a lower cutoff point, 0.54 (AUC=0.856, CI 95.0%: 0.78-0.91), sensitivity of 0.84 and specificity of 0.78 [11].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…7 The LAP index may thus constitute an abdominal adiposity marker that correlates with central lipid accumulation. 8 Since the LAP index was first proposed, in Kahn's pioneering study, 9 many researchers have used it to predict cardiovascular risk in different populations, such as among patients with type 2 diabetes 6 or insulin resistance, 10 women with polycystic ovarian syndrome 10,11 and hospital outpatients 12 and inpatients. 7 However, no studies have evaluated the use of this index among patients attending primary care units.…”
Section: Introductionmentioning
confidence: 99%
“…DIPOSITY IS AN INDEPENDENT PREDICTOR OF metabolic diseases, which makes its measurement crucial. 1,2 Body fat percentage (%BF) can be measured accurately and precisely using dualenergy x-ray absorptiometry (DEXA). 3 However, such equipment is expensive and bulky, 4 which makes it inconvenient for use in community health screening settings.…”
mentioning
confidence: 99%